2012
DOI: 10.1192/bjp.bp.109.066357
|View full text |Cite
|
Sign up to set email alerts
|

Preventing progression to first-episode psychosis in early initial prodromal states

Abstract: Integrated psychological intervention appears effective in delaying the onset of psychosis over a 24-month time period in people in an EIPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
191
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(206 citation statements)
references
References 43 publications
(105 reference statements)
4
191
0
11
Order By: Relevance
“…He might have taken a major interest in the wealth of research findings on early intervention, and that might have added to his therapeutic optimism [33]. However, he might have spent even more time in understanding the implementation gap, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…He might have taken a major interest in the wealth of research findings on early intervention, and that might have added to his therapeutic optimism [33]. However, he might have spent even more time in understanding the implementation gap, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The first compared supportive psychotherapy in an unblinded trial of an integrated treatment package of family support, cognitive behavioral therapy, low-dose Risperidone and computerized training across a range of domains using CogPack. 15 After 12 months, the active treatment group (N = 51) had a lower transition rate to psychosis (3.2%) than the treatment as usual group (16.9%, N = 57), with continued differences after 24 months. 15 While these results were quite promising, effects on cognition were not reported, nor was it possible to assess the relative impact of the individual treatment components in the active condition.…”
Section: Introductionmentioning
confidence: 99%
“…15 After 12 months, the active treatment group (N = 51) had a lower transition rate to psychosis (3.2%) than the treatment as usual group (16.9%, N = 57), with continued differences after 24 months. 15 While these results were quite promising, effects on cognition were not reported, nor was it possible to assess the relative impact of the individual treatment components in the active condition. Two single-sample pilot studies of cognitive training in CHRs have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Convergent findings were reported from studies that had evaluated cognitive behavioral therapy without concomitant antipsychotics vis-à-vis more unspecific supportive treatment measures. Morrison et al (2004) in the UK, Addington et al (2011a) in Canada, as well as Bechdolf et al (2012) in Germany have performed such studies. With the exception of Addington et al (2011a), who found no group differences, probably due to small sample size and generally low conversion rates, all of these trials demonstrated lower conversion rates in the experimental treatment group, supporting the hypothesis that specific psychotherapeutic interventions also reduce or delay the risk of converting to full-blown psychosis in individuals suffering from prodromal symptoms.…”
Section: Psychosocial Interventionsmentioning
confidence: 96%